PENGARUH BUDAYA ORGANISASI, PENDIDIKAN DAN PELATIHAN TERHADAP MOTIVASI DAN KINERJA PEGAWAI DI INSPEKTORAT KABUPATEN KLATEN - Erma Widyastuti; Ismail, Habib (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2024)
The aim of this research is to determine whether there is an influence of organizational culture, education and training on employee motivation and performance at the Klaten Regency Inspectorate, either partially or simultaneously. The population taken for this research were 45 employees at the Klaten Regency Inspectorate. Samples were taken using a simple random sampling method, while the research instruments used were questionnaires and a list of questions. Hypothesis testing uses the path analysis method with the help of SPSS 20.0 (Statistical Package for Social Science) software. The research results show that both partially and simultaneously organizational culture, education and training have a positive and significant effect on competence and directly or indirectly also have a positive and significant impact on employee motivation and performance at the Klaten Regency Inspectorate. The most dominant variable influencing motivation and performance is the Organizational Culture Variable. This research has limitations in the variables used, the independent variables are: organizational culture, training and motivation as intervening variables. Meanwhile, the dependent variable is employee performance. Meanwhile, there are still many variables that influence performance.